2020
DOI: 10.3390/membranes10100268
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Hemoglobin Enzymatic Hydrolysis by a New Eco-Efficient Process-Part II: Production of Bioactive Peptides

Abstract: Bovine cruor, a slaughterhouse waste, was mainly composed of hemoglobin, a protein rich in antibacterial and antioxidant peptides after its hydrolysis. In the current context of food safety, such bioactive peptides derived from enzymatic hydrolysis of hemoglobin represent potential promising preservatives for the food sector. In this work, the hemoglobin hydrolysis to produce bioactive peptides was performed in a regulated pH medium without the use of chemical solvents and by an eco-efficient process: electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 49 publications
(54 reference statements)
3
29
2
Order By: Relevance
“…Moreover, the α137-141 peptide derived from bovine cruor waste has been demonstrated to be a promising natural substitute for the synthetic additives widely used to protect meat during storage and distribution by reducing lipid oxidation by 60% and inhibiting growth of total viable colonies, yeasts and molds [ 10 ]. Furthermore, the biological properties (antibacterial, antifungal and antioxidant) of bovine hemoglobin hydrolysates from bovine blood slaughterhouse waste, produced using an innovative and green process: electrodialysis with bipolar membrane (EDBM), have been proven [ 11 ]. However, further experiments were needed to: (1) settle the issue of membrane fouling that appeared during the production of hydrolysates as explained by Abou-Diab et al [ 12 ]; (2) remove, by discoloration, the heme contained in the hydrolysates, which is responsible for the red color of blood and makes product valorization difficult due to iron oxidation; and (3) reduce the final mineral salt concentration to be able to meet consumer demands.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the α137-141 peptide derived from bovine cruor waste has been demonstrated to be a promising natural substitute for the synthetic additives widely used to protect meat during storage and distribution by reducing lipid oxidation by 60% and inhibiting growth of total viable colonies, yeasts and molds [ 10 ]. Furthermore, the biological properties (antibacterial, antifungal and antioxidant) of bovine hemoglobin hydrolysates from bovine blood slaughterhouse waste, produced using an innovative and green process: electrodialysis with bipolar membrane (EDBM), have been proven [ 11 ]. However, further experiments were needed to: (1) settle the issue of membrane fouling that appeared during the production of hydrolysates as explained by Abou-Diab et al [ 12 ]; (2) remove, by discoloration, the heme contained in the hydrolysates, which is responsible for the red color of blood and makes product valorization difficult due to iron oxidation; and (3) reduce the final mineral salt concentration to be able to meet consumer demands.…”
Section: Introductionmentioning
confidence: 99%
“…However, the hurdles are still high when dealing with scale-ups and real-life conditions. In their papers, Abou Diab et al [ 5 , 8 ] developed and proposed a new green application of EDBM to the production of bioactive peptides from a by-product of slaughterhouses, which fits perfectly with the concept of a circular economy. Indeed, hemoglobin from blood, once hydrolyzed, allows the bioproduction of active peptides that can then be reused on meat or meat products to increase their preservation and inocuity.…”
mentioning
confidence: 97%
“…The optimal ED desalination conditions were at a current density of 5 mA/cm 2 and pH of 5, with a 64% desalination rate, a 29.8% amino acid loss rate, and that without compromising the original flavor. With the goal of producing a bioactive hydrolysate, from bovine cruor, a slaughterhouse waste, Abou Diab et al [ 5 , 8 ], developed a new membrane-based hydrolysis process. In these studies, EDBM was demonstrated for the first time as an ecoefficient and innovative technology to produce peptide hydrolysates from enzymatic hydrolysis of bovine hemoglobin with low mineral salt concentration.…”
mentioning
confidence: 99%
“…Its useful components can promote host health by modifying gut microbiota composition (Nakajima et al, 2018), which is crucial for improving immune function (Belkaid & Hand, 2014;Wlodarska et al, 2011). Moreover, microbial metabolites could affect the immune response, thus inhibiting pathogens and suppressing inflammation (Rist et al, 2013;Rooks & Garrett, 2016).Haemoglobin in animal blood has antibacterial activities against pathogens and can be used as a source of bioactive peptides (Abou-Diab et al, 2020). These activities of intact haemoglobin are improved in haemoglobin peptides produced by enzyme-catalysed reactions (Pakdeesuwan et al, 2016).…”
mentioning
confidence: 99%
“…Haemoglobin in animal blood has antibacterial activities against pathogens and can be used as a source of bioactive peptides (Abou-Diab et al, 2020). These activities of intact haemoglobin are improved in haemoglobin peptides produced by enzyme-catalysed reactions (Pakdeesuwan et al, 2016).…”
mentioning
confidence: 99%